Young carers in receipt of Carer Payment and Carer Allowance 2001 to 2006: characteristics, experiences and post-care outcomes - Bray, J Rob (My University, 2013)
This paper aims to provide a better understanding of the circumstances of young people (aged under 25 years) who receive transfer payments to support them in providing ‘informal’ care to people with disabilities and the frail aged. A specific motivation of the research was to examine the extent to which young carers are reliant on income support, both while caring and post-care, and their education participation.
Keywords: Disability & Carers -- Care of Disabled; Life Events -- Caring for frail elderly / disabled; Benefits and Payments -- Income support; Children -- Adolescents and youth; Education and Training; Adolescents and youth; Disadvantage, adversity and resilience; Income, wealth and finances; Benefits and Payments; Life Events; Disability & Carers; Children; Education and Training; Caring for frail elderly / disabled; Adolescents and youth; Care of Disabled; Income support; Adolescents and youth; Dsiadvantage, adversity and resilience; Income, wealth and finances; Adversity and resilience